2019
DOI: 10.1111/liv.14223
|View full text |Cite
|
Sign up to set email alerts
|

Biology and significance of alpha‐fetoprotein in hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC) is one of the most common causes of cancer-related deaths globally due, in part, to the majority of patients being diagnosed with intermediate or advanced stage disease. Our increased understanding of the heterogeneous molecular pathogenesis of HCC has led to significant developments in novel targeted therapies. Despite these advances, there remains a high unmet need for new treatment options. HCC is a complex disease with multiple pathogenic mechanisms caused by a variety of ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

16
321
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 418 publications
(339 citation statements)
references
References 148 publications
16
321
0
2
Order By: Relevance
“…5 Alpha-fetoprotein (AFP), one of the first protein tumor markers, has been widely used and accepted since its discovery > 60 years ago. 6,7 However, it has low sensitivity and specificity in predicting the prognosis of HCC and has no diagnostic value in small HCCs. 8 The tumor-node-metastasis (TNM), Barcelona Clinic Liver Cancer (BCLC), Cancer of the Liver Italian Program (CLIP), and Okuda staging systems have been commonly used in stratifying and assessing the prognosis of HCC.…”
Section: Introductionmentioning
confidence: 99%
“…5 Alpha-fetoprotein (AFP), one of the first protein tumor markers, has been widely used and accepted since its discovery > 60 years ago. 6,7 However, it has low sensitivity and specificity in predicting the prognosis of HCC and has no diagnostic value in small HCCs. 8 The tumor-node-metastasis (TNM), Barcelona Clinic Liver Cancer (BCLC), Cancer of the Liver Italian Program (CLIP), and Okuda staging systems have been commonly used in stratifying and assessing the prognosis of HCC.…”
Section: Introductionmentioning
confidence: 99%
“…Alpha-fetoprotein (AFP), a secreted 70 kD glycoprotein, has been used as a biomarker for HCC as elevated expression of AFP in tumors and serum is found in 60-80% of HCC patients and correlates with poor prognosis (13). AFP is commonly expressed in the fetal liver and yolk sac during the first trimester of pregnancy, but declines sharply after birth and remains low in adulthood (13).…”
Section: Introductionmentioning
confidence: 99%
“…Alpha-fetoprotein (AFP), a secreted 70 kD glycoprotein, has been used as a biomarker for HCC as elevated expression of AFP in tumors and serum is found in 60-80% of HCC patients and correlates with poor prognosis (13). AFP is commonly expressed in the fetal liver and yolk sac during the first trimester of pregnancy, but declines sharply after birth and remains low in adulthood (13). While vital for the developing fetus, the role of AFP in adult tissues is less well-understood but appears dispensable, thus making it a promising tumor antigen for T cell-based immunotherapies (13).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…US is an inexpensive, non-invasive, and highly available surveillance method recommended by the most relevant scientific societies involved the in HCC management. [3][4][5] Undoubtedly, the detection of HCC by US in a cirrhotic liver might be limited by several factors, including coarse liver parenchyma that difficult nodule detection, the increasingly frequent obesity as a main driver of cirrhosis in Western countries associated to inadequate ultrasound beam penetration, 13 15,16 Given the widespread use of US, large-scale randomized controlled trials in developed countries aimed to confirm the benefit of HCC surveillance in terms of survival are largely impractical due to ethical concerns in randomizing patients at risk for HCC to a no-intervention group and the sheer difficulty of including subjects after informed consent of the potential benefits/risks is requested. 17 For that reason, studies as the one reported by Chen et al 9 showing the benefits of surveillance are very supportive, and call the attention for the operator dependency of US, the importance of high-quality training and performance and the urgent need of broader adherence and adoption of guidelines.…”
mentioning
confidence: 99%